Postoperative Length of Hospital Stay following Open Appendectomy in a Tertiary Care Children’s Hospital - Yadav, Shailendra Kumar; Gyawali, Pratik; Singh, Raj Kumar; Bhattarai, Nabin; Simkhada, Prashant; Basnet, Bal Mukund (Grande Medical Journal, 2025)
Background: Appendicitis is a common pediatric surgical emergency. But at our hospital setting, only an open appendectomy is done in the pediatric population. Surgery is the preferred treatment for complicated appendicitis cases. Laparoscopic appendectomy has been associated with shorter recovery and fewer postoperative complications in children with acute appendicitis. Our study focus the impact of hospital stay following open appendectomy in pediatric patients. Method: The cross-sectional retrospective study was performed in the tertiary care children’s hospital in Nepal using medical records from the anesthesia register, surgical ward and operation room. A total of 128 pediatric cases were studied and analyzed. Result: The average length of hospital stay was found to be 4.53± 2.2 days. The mean length of stay in non- perforated was 4.08±1.5 days whereas in perforated cases was 7.35 ±3.6 days ( t = 3.7, p = 0.0019) Conclusion: In our tertiary hospital, the children who were undergoing open appendectomy had a higher length of stay till discharge in case of perforated appendicitis. Early confirmation of disease and timely surgical interventions help to minimize complications and shorten the hospital stay. These findings may help inform institutional planning and resource allocation for pediatric surgical services.